2022
DOI: 10.3389/fpls.2022.1020832
|View full text |Cite
|
Sign up to set email alerts
|

Biochar application ameliorated the nutrient content and fungal community structure in different yellow soil depths in the karst area of Southwest China

Abstract: The influence of biochar on the change of nutrient content and fungal community structure is still not clear, especially in different yellow soil depths in karst areas. A soil column leaching simulation experiment was conducted to investigate the influence of biochar on soil content, enzymatic activity, and fungal community diversity and structural composition. Three biochar amounts were studied, namely, 0%(NB, no biochar), 1.0%(LB, low-application-rate biochar), and 4.0% (HB, high-application-rate biochar). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Our results are consistent with the widely accepted notion that nitrogen forms substantially impact the growth and yield of tomatoes. Recent research, including [38,39], has demonstrated that the efficacy of nutrient uptake and plant growth can be enhanced through using mixed nitrogen sources. In particular, research [40] demonstrated that the physiological functions of tomatoes are enhanced, resulting in an increase in yield and quality, when the ammonium-to-nitrate ratio is balanced.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the widely accepted notion that nitrogen forms substantially impact the growth and yield of tomatoes. Recent research, including [38,39], has demonstrated that the efficacy of nutrient uptake and plant growth can be enhanced through using mixed nitrogen sources. In particular, research [40] demonstrated that the physiological functions of tomatoes are enhanced, resulting in an increase in yield and quality, when the ammonium-to-nitrate ratio is balanced.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, biochar serves as a habitat for beneficial microorganisms that play a pivotal role in nutrient cycling and mineralization. These microbes contribute to breaking down organic matter, rendering nutrients like N, P, and K more abundant and accessible to plants [91]. Additionally, when used in combination with specific microorganisms such as AMF, biochar can enhance nutrient uptake.…”
Section: Effects Of Biochar and Biochar With Amf On Soil Chemical Pro...mentioning
confidence: 99%
“…Similar studies have been conducted using biochar. Biochar can improve soil fertility and reduce the occurrence of diseases and pests by improving the soil microbial environment [20][21][22][23][24][25]. At present, PGPR and biochar are extensively utilized as vital soil amendment materials in agricultural production [26,27].…”
Section: Introductionmentioning
confidence: 99%